Pengaruh Literasi Keuangan, Pengetahuan Keuangan Dan Sikap Keuangan Terhadap Perilaku Manajemen Keuangan Pada Pelaku Umkm Kuliner Di Kabupaten Sukoharjo - Wardhani, Byan Satia; Irawati, Zulfa (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The micro, small, and medium enterprises (MSMEs) sector has an important role in economic growth in Indonesia. MSMEs have a great influence on the country's economic growth because MSMEs can reduce the unemployment rate by growing new businesses which will later open job vacancies for the community and improve social welfare (Nadhiroh & Hermawan, 2024). This is also supported by a positive and enthusiastic public response to the existence of MSMEs. Competition between various businesses cannot be prevented in the business world. This type of research is a type of quantitative research, this study is also an explanatory research with a sample of 160 respondents. With results of 1) Financial Literacy has a positive and significant effect on Financial Management Behavior (The first hypothesis is accepted). 2) Financial Knowledge has a positive and significant effect on Financial Management Behavior (The second hypothesis is accepted). 3) Financial Attitudes have a positive and significant effect on Financial Management Behavior (The third hypothesis is accepted). 4) Financial Literacy, Financial Knowledge, and Financial Attitudes affect Financial Management Behavior together. 5) Financial Literacy, Financial Knowledge, and Financial Attitudes affect Financial Management Behavior by 24.2%.